2014
DOI: 10.3126/nepjoph.v6i1.10760
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and awareness of diabetic retinopathy among admitted diabetic patients at a tertiary level hospital in Kathmandu

Abstract: The prevalence of DR was 38 % among the admitted diabetic cases and the DR was significantly associated with the duration of diabetes and systemic hypertension. Almost half of the cases had been unaware of DR before referral. This emphasizes the importance of the collaboration of the physician and the ophthalmologist for an early DR detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 17 publications
1
30
1
Order By: Relevance
“…This could explain the association between diabetes and retinopathy observed in the present study. Thapa et al, [3], Thomas et al, [19], Jingi et al, [20] highlighted the same association. The imbalance of diabetes was a risk factor for complications.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This could explain the association between diabetes and retinopathy observed in the present study. Thapa et al, [3], Thomas et al, [19], Jingi et al, [20] highlighted the same association. The imbalance of diabetes was a risk factor for complications.…”
Section: Discussionmentioning
confidence: 60%
“…Yang et al, [18] found the same association between physical activity level and retinopathy. In opposite, Thapa et al, [3] have reported that there is any association between tobacco consumption and retinopathy. The association between hypertension and diabetic retinopathy was variously appreciated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Doctors and family members were the predominant source for awareness of DR in our study, similar to studies conducted in India [ 11 , 20 ]. Studies conducted among diabetics attending a hospital have almost always shown a higher awareness (67–87 %) of DR in Nepal and other countries [ 12 , 21 – 24 ]. A more comprehensive health care strategy, including timely referral to an ophthalmologist by physicians and other eye care providers, could potentially lead to a higher rate of awareness.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with findings reported from many parts of the world that between 25 and 50% of persons with diabetes present with visual loss at the first visit to an eye facility. [ 19 20 21 ] In a long-standing condition like diabetes, compliance with medication and follow-up is a major problem. Therefore, educational/counseling interventions for persons with diabetes should emphasize the critical importance of regular medication and glycemic control as well as the need for regular retinal examination even if they do not have symptoms of visual loss.…”
Section: Discussionmentioning
confidence: 99%